2014
DOI: 10.1002/jmv.24067
|View full text |Cite
|
Sign up to set email alerts
|

Direct role of antibody‐secreting B cells in the severity of chronic hepatitis B

Abstract: Chronic hepatitis B involves different immune cells. The direct role of antibody-secreting B cells in the severity of chronic hepatitis B unclear. In this study, the number of plaque forming cells [PFC-(IgG, IgM, anti-HBc IgG, and anti-HBc IgM)], liver function tests (LFT) [alkaline phosphatase (ALP), alanine aminotransferase (ALT), and total serum bilirubin (TSB)], the levels of IL-10 in sera and in lymphocyte cultures, the number of CD4(+) and CD8(+) cells were measured in the peripheral blood of patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…We also found that the serological IgG levels were significantly higher in patients with CHB than that in healthy subjects. The result was comparable to the previous reports in which the high levels of antibody‐secreting B cells and the antibodies play an important role in the severity of CHB . However, it has been reported that in patients with CHB, the neutralizing antibodies (anti‐HBs) are important for virus control and disease resolution, while HBsAg‐specific IgG‐secreting B cells are limited .…”
Section: Discussionsupporting
confidence: 85%
“…We also found that the serological IgG levels were significantly higher in patients with CHB than that in healthy subjects. The result was comparable to the previous reports in which the high levels of antibody‐secreting B cells and the antibodies play an important role in the severity of CHB . However, it has been reported that in patients with CHB, the neutralizing antibodies (anti‐HBs) are important for virus control and disease resolution, while HBsAg‐specific IgG‐secreting B cells are limited .…”
Section: Discussionsupporting
confidence: 85%
“…During a cellular immune response, the T lymphocytes subgroups such as CD4 + and CD8 + cells respond to this virus and can directly cause the persistent inflammation of chronic hepatitis B 1 . However, the role of B-lymphocytes in the severity of chronic hepatitis B is unclear 22 . A recent study reported that high prevalence of activated B cells plays a crucial role in the progression of CHB infection by B lymphocytes-mediated immune response to HBV 23 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that high prevalence of activated B cells plays a crucial role in the progression of CHB infection by B lymphocytes-mediated immune response to HBV 23 . Hepatitis B core protein (HBcAg) is the most immunogenic HBV antigen, and its antibody, anti-HBc secreted via the activated antibody-secreting B cells directly play an important role in the severity of chronic hepatitis B by hepatocytotoxic response 22 . Furthermore, Li et al .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic HBV infection is a major risk factor for the development of HCC, which accounts for ~50% of all HCC cases. The pathogenesis of HBV virus-induced HCC has been previously reported to be primarily regulated by the chronic liver inflammation during the HBV infection, particularly the dysfunction of B and T cells (28,29). B cells are a major part of the lymphocyte-mediated humoral immunity and are associated with antibody production, directly contributing to the clearance of HBV.…”
Section: Discussionmentioning
confidence: 99%
“…Clearance of hepatitis B infection is directly performed by B cells by secretion of specific antibodies, this function is primarily mediated by T follicular helper (Tfh) cells. The dysfunction of Tfh and B cells has been associated with the pathogenic process of various autoimmune diseases and tumors (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%